To develop a new mineral carbonation process that have a high efficiency in CO2 absorption into industry slag using low energy mechanical milling - Muhd Nor, Nik Hisyamudin (2021)
Increase in the CO2 emission in atmosphere due to the combustion of fossil fuels has caused serious global warming. Electricity generation, tranportation, and industrial waste are the main sectors indentified to contribute to the emission of CO2 in Malaysia. In dealing with this issue, the absorption of CO2 into industrial waste was experimentally studied by the utilization of mechanical grinding method. This research is to aim a development of new mineral carbonation process that has a high efficiency in the capture and storage of CO2 with low energy consumption. In the first stage of this study, the behavior of CO2 absorption on electric arc furnace and ladle furnace slag was studied by low energy mechanical milling It was found that the absorption is occured during milling. CO2 was stored into the slag mainly as CaCO3. Thus this indicates that the CO2 can be stored permanently inside the slag with this method. In the next stage, the effect of dissolution of metal element into water on the behavior of CO2 absorption was investigated by leaching test experiment. It was found that , concentration value of Fe in pure water is higher but in river water the concentration is lower, the dissolve concentration decreased with the increased in the number of the leaching time. Concentration will be increased at the earlier stage before it decreased at final of concentration. This case because the liquid became saturated and cannot be to dissolved. After the pH steeply increased gradually at an early stage of the elution of slag, it slightly decreased. The pH decreased with the increased in the number of elution. The changes of pH in leaching test it seemed to depend on the content of CaO in the slag. For mechanism of CO2 absorption, morphological change of slag were study and the slag were characteried by using XRD, FE-SEM, and EDS.